Analyze Efect of Employee Integrity, Organizational Commitment, and Work Motivation on Sustainable Employee Performance, with Job Satisfaction as a Mediating Variable among Employees at PKS 4 of PT. Dharma Satya Nusantara Tbk - Muttaqin, Khamdan; Arijanto, Agus (IJOSMAS, 2025)
This study aims to analyze efect of employee integrity, organizational commitment, and work motivation on sustainable employee performance, with job satisfaction as a mediating variable among employees at PKS 4 of PT. Dharma Satya Nusantara Tbk. A quantitative approach was used, employing a questionnaire distributed to 110 respondents. Data collection measured variables such as employee integrity, organizational commitment, work motivation, job satisfaction, and sustainable employee performance. Data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results indicate that employee integrity, organizational commitment, and work motivation have a positive and significant effect on sustainable employee performance. Furthermore, job satisfaction significantly mediates the effect of employee integrity, organizational commitment, and work motivation on sustainable employee performance. These findings suggest that employee integrity, organizational commitment, and work motivation play an essential role in fostering sustainable employee performance, particularly among the employees of PKS 4 at PT. Dharma Satya Nusantara Tbk. Keywords: Employee Integrity, Organizational Commitment, Work Motivation, Sustainable Employee Performance, Job Satisfaction.